2013
DOI: 10.1002/star.201200262
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic response to frozen stored wholemeal-flour rolls enriched with fresh sourdough and whey proteins

Abstract: The aim of this study was to examine the effect of addition of fresh sourdough and whey proteins to partially baked and frozen wholemeal wheat‐flour rolls on the glycaemic index (GI). The study was performed on healthy humans (n = 15). Each human tested five types of wholemeal wheat rolls: (1) fully baked, non‐frozen (FBNF), (2) partially baked and frozen (PBF), (3) fully baked, non‐frozen with the addition of fresh sourdough (FBNF + FS), (4) partially baked and frozen with the addition of fresh sourdough (PBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The values with different letters in rows are significantly different at p < 0.05. RDS contents obtained in this study were within the range proposed by other authors [9,13,19]. However, elderberry, seabuckthorn and rowan breads had significantly lower contents of this fraction compared with the control bread (p < 0.05) (Table 3), elderberry and sea-buckthorn enriched breads having the lowest content (p < 0.05).…”
Section: Starch Digestibility Of the Tested Breadssupporting
confidence: 87%
See 1 more Smart Citation
“…The values with different letters in rows are significantly different at p < 0.05. RDS contents obtained in this study were within the range proposed by other authors [9,13,19]. However, elderberry, seabuckthorn and rowan breads had significantly lower contents of this fraction compared with the control bread (p < 0.05) (Table 3), elderberry and sea-buckthorn enriched breads having the lowest content (p < 0.05).…”
Section: Starch Digestibility Of the Tested Breadssupporting
confidence: 87%
“…The obtained results show their concordance with the data presented in the literature: dry matter 50-86.3 g/100 g, protein 10.3-12.5 g/100 g d.m., fat 0.7-2.8; total dietary fiber 6.9-13.5 g/100 g d.m., and ash 1.5-4.7 g/100 g d.m. [9,19,20]. However, it is worth mentioning that the fruit-enriched breads had higher nutritional value due to significantly higher contents of fat and dietary fiber as well as ash in comparison with the control bread (p < 0.05).…”
Section: Chemical Compositionmentioning
confidence: 94%
“…According to the literature data, the content of dry matter in wheat bread ranged between 51 and 86.3% . Dry matter of the tested rolls was within this range (Table ).…”
Section: Resultsmentioning
confidence: 70%
“…Bárcenas et al [1] has reported dry matter losses when wheat bread was stored in a frozen state for a period of 42 days. Similarly, wheat-flour rolls baked by bakeoff technology (partially baked) had significantly lower content of dry matter, as compared with traditionally baked rolls in the study by Borczak et al [19][20][21].…”
Section: ]mentioning
confidence: 85%
See 1 more Smart Citation